Incident Reports. Themes developed in the Press - Rodríguez Carcela, Rosa María (2011)
The article analyzes and describes the thematic contents of incident reports in the press. Incident reports belong to the area of specialized journalism, because of the topic it deals and broadcasts. Most of its contents are related to bad news. The two major thematic categories of incident reports are crimes and accidents. The types of incidents that are mainly featured in the press are homicides, traffic accidents, drug dealing and burglary.